Introduction and dispersal of Epidinocarsis lopezi (Hym., Encyrtidae), an exotic parasitoid of the cassava mealybug, Phenacoccus manihoti (Hom., Pseudococcidae), in Africa - Herren, H.R.; Neuenschwander, Peter; Hennessey, R.D.; Hammond, W.N.O. (Elsevier, 1987)
In 1981 the South American parasitoid Epidinocarsis lopezi (DeSantis) was imported into Nigeria for control of the cassava mealybug, Phenacoccus manihoti Mat.-Ferr. It was multiplied in an insectary at the International Institute of Tropical Agriculture (IITA), Ibadan, and first released in 1981/82. Within 3 years it dispersed over 200 000 km2 in southwestern Nigeria, occupying between 70 and 98% of all fields. By December 1985, a total of over 50 releases in 34 regions had been made in 12 African countries. E. lopezi was already established in 28 regions, and in some cases E. lopezi spread across international borders. It now occupies 650 000 km2 in 13 countries: 420 000 km2 in West Africa, 210 000 km2 in Central Africa and several small disjunct territories, covering a range of ecological zones (Sudan Savannah, Guinea Savannah, Equatorial Rainforest, Highlands).